A new scheme for RPL to handle mobility in wireless sensor networks. (2019) - Gara, Fatma; Saad, Leila Ben; Ayed, Rahma Ben; Tourancheau, Bernard
Mobile wireless sensor networks (WSNs) are characterised by dynamic changes in the network topology leading to route breaks and disconnections. The IPv6 routing protocol for low power and lossy networks (RPL), which has become a standard, uses the Trickle timer algorithm to handle changes in the network topology. However, neither RPL nor Trickle timer are well adapted to mobility. This paper investigates the problem of supporting mobility when using RPL. It enhances RPL to fit with sensors' mobility by studying two cases. Firstly, it proposes to modify RPL in order to fit with a dynamic and hybrid topology in the context of medical applications. Secondly, it investigates a more general case and introduces a new adaptive timer for RPL. The proposed approach is validated through extensive simulations and compared with existing protocols in the literature. Results show that our proposal significantly reduces disconnections and increases packet delivery ratio while maintaining low overhead.